Experimental study on beam-to-column connections with reduced beam section against progressive collapse. (December 2020) - Qiao, Huiyun; Chen, Yu; Wang, Jinpeng; Chen, Canwen
Abstract: Steel frame structures with ordinary weld connections often suffer from brittle fractures; to mitigate this issue, measures have been taken to integrate plastic hinges and improve the ductility of the steel connections. A new reduced beam section (RBS) connection, consisting of radius cuts in the beam flanges and circular openings in the beam webs, is proposed to allow for more ductile connections. RBS connections may increase structural deflection and crack width in the steel frame structure under large deformations. Therefore, it is extremely important to consider the bearing capacity and progressive collapse resistance of steel frame structures with RBS connections. In this study, nine different specimens with double-span frames were constructed and tested under a central column removal scenario: one without an RBS (RBS0), one with flange reductions (RBS1), and seven with web and flange reductions (RBS2). The mechanical behaviours of the different specimens were determined, including their failure modes, vertical force-deformation responses, and contribution of catenary action to resist progressive collapse. The results indicated that the RBS0 specimen with brittle failure did not effectively resist progressive collapse. RBS1 exhibited superior ductility and resistance compared to RBS0; however, its resistance to progressive collapse after cracking required further improvement. RBS2 with web openings formed an arch structure to dissipate energy through continuous deformations. Further, two important factors in RBS2 that influenced its mechanical properties were the diameter and the distance of the web opening, which were related to the development of arching and catenary action. Graphical abstract: Unlabelled Image Highlights: Tests are conducted on specimen groups with or without reduced beam sections. Specimens with flange reductions, and with web and flange reductions are included. Various fracture and failure modes occur for the connection types. The web opening diameter and distance influence the mechanical properties. The web openings form an arch structure to dissipate energy through deformation.